Development of selective, ultra-fast multiple co-sensitization to control dye loading in dye-sensitized solar cells - Peter Holliman (RSC Advances, 2014)
Enhancing the spectral response of dye-sensitized solar cells (DSC) is essential to increasing device efficiency and a key approach to achieve this is co-sensitization (i.e. the use of multiple dyes to absorb light from different parts of the solar spectrum). However, precise control of dye loading within DSC mesoporous metal oxide photo-anodes is non-trivial especially for very rapid processing (minutes). This is further complicated by dyes having very different partition (Kd) and molar extinction (ε) coefficients which strongly influence dye uptake and spectral response, respectively. Here, we present a highly versatile, ultra-fast (ca. 5 min) desorption and re-dyeing method for dye-sensitized solar cells which can be used to precisely control dye loading in photo-electrode films. This method has been successfully applied to re-dye, partially desorb and re-dye and selectively desorb and re-dye photo-electrodes using examples of a Ru-bipy dye (N719) and also organic dyes (SQ1 and D149) giving η up to 8.1% for a device containing the organic dye D149 and re-dyed with the Ru dye N719. The paper also illustrates how this method can be used to rapidly screen large numbers of dyes (and/or dye combinations) and also illustrates how it can also be used to selectively study dye loading.